2022
DOI: 10.3390/polym14183736
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability Assessment of Polyester Copolymers Based on Poly(ethylene adipate) and Poly(ε-caprolactone)

Abstract: Biodegradable polymers contain chains that are hydrolytically or enzymatically cleaved, resulting in soluble degradation products. Biodegradability is particularly desired in biomedical applications, in which degradation of the polymer ensures clearance from the body and eliminates the need for retrieval or explant. In this study, a homologues series of poly(ε-caprolactone)-b-poly(ethylene adipate)-b-poly(ε-caprolactone) (PCL-b-PEA-b-PCL) block copolymers, with constant PEA molar mass and different PCL sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Another example of biodegradable polyesters ( M w up to 285 kDa) includes the use of biobased monomers, such as ethylene brassylate- b - δ -hexalactone, wherein a branched comonomer favors an amorphous arrangement, which has an impact on the mechanical properties, giving rise to possible applications in cell culture scaffolds [ 13 ]. On the other hand, triblock copolymers consisting of ethylene oxide- b - ε -caprolactone- b -γ-butyrolactone and ε -caprolactone- b -ethylene adipate- b - ε -caprolactone have also been reported; these synthesized copolyesters with M n up to 12.3 and 23.2 kDa, respectively, offer drug delivery system capabilities with specific drug-release profiles [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another example of biodegradable polyesters ( M w up to 285 kDa) includes the use of biobased monomers, such as ethylene brassylate- b - δ -hexalactone, wherein a branched comonomer favors an amorphous arrangement, which has an impact on the mechanical properties, giving rise to possible applications in cell culture scaffolds [ 13 ]. On the other hand, triblock copolymers consisting of ethylene oxide- b - ε -caprolactone- b -γ-butyrolactone and ε -caprolactone- b -ethylene adipate- b - ε -caprolactone have also been reported; these synthesized copolyesters with M n up to 12.3 and 23.2 kDa, respectively, offer drug delivery system capabilities with specific drug-release profiles [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing degradable plastics, ideally made from renewable resources, is the obvious the first step in addressing this problem. The class of polyesters with (bio)degradable qualities now dominates various application domains [ 7 , 8 , 9 ]. Different types of enzymes, such as esterase, cutinase, and lipase, are known as being highly active for the degradation of polyester-based polymers [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported the significance of a few Food and Drug Administration (FDA)-approved block polymers such as poly(ɛ-caprolactone) (PCL), polylactic acid (PLA), polyglycolic acid (PGA) and polylactic acid-co-glycolic acid (PLGA) due to their biocompatibility, low cost and biodegradability [ 4 , 5 , 6 , 7 ]. A rising research interest in long-term implantable drug delivery systems for a semi-crystalline degradable polymer PLA is mentioned in the reported studies due to its good accelerating rate of bio-absorption, low cost and ease of availability.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is mostly governed by hydrophobic interactions (though in few cases other non-covalent interactions may also operate) in comparison to conventional low molecular weight surfactants [ 1 , 2 , 3 ]. However, the nature and the molecular composition of blocks and the selectivity of the solvent influences the formation and morphology of nanoaggregates [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation